2013
DOI: 10.1016/j.cub.2013.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mir-92a Underlies Natural Morphological Variation in Drosophila melanogaster

Abstract: SummaryIdentifying the genetic mechanisms underlying phenotypic change is essential to understanding how gene regulatory networks and ultimately the genotype-to-phenotype map evolve. It is recognized that microRNAs (miRNAs) have the potential to facilitate evolutionary change [1–3]; however, there are no known examples of natural morphological variation caused by evolutionary changes in miRNA expression. Therefore, the contribution of miRNAs to evolutionary change remains unknown [1, 4]. Drosophila melanogaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 29 publications
8
79
0
Order By: Relevance
“…miR-8 mutants showed leg and wing defects resulting from difficulties in eclosion from the pupal case (Karres et al, 2007). Differential expression of miR-92a in different strains of Drosophila correlates with the pattern of trichomes on the femur of the second leg, and miR-92a overexpression has been shown to lead to loss of trichomes (Arif et al, 2013). Consistent with this, Table 2.…”
Section: Other Developmental Defectssupporting
confidence: 61%
“…miR-8 mutants showed leg and wing defects resulting from difficulties in eclosion from the pupal case (Karres et al, 2007). Differential expression of miR-92a in different strains of Drosophila correlates with the pattern of trichomes on the femur of the second leg, and miR-92a overexpression has been shown to lead to loss of trichomes (Arif et al, 2013). Consistent with this, Table 2.…”
Section: Other Developmental Defectssupporting
confidence: 61%
“…Furthermore, it has been shown that changes in cis -regulatory sequences of svb and changes at the Ultrabithorax locus underlie the evolution of larval and leg trichome patterning, respectively, between species (Stern 1998; McGregor et al 2007). However, a recent study has shown that intraspecific variation in leg trichome patterns in Drosophila melanogaster is caused by changes in the expression of a microRNA, mir-92a (Arif et al 2013), which represses expression of shavenoid , a downstream target of svb (Schertel et al 2012; Arif et al 2013). The study by Arif and colleagues, therefore, not only revealed the genetic basis for morphological change, but also provided new insights into a well-characterized developmental GRN.…”
Section: Insights From Micro-evo-devomentioning
confidence: 99%
“…The sequencing depth of the small RNA libraries was ~25M reads, with ~14M reads matching to the reference genome, full length, with no mis-matches or gaps allowed. The abundances of the reads were normalized using the reads per total method (22)(23)(24). The replicate to replicate differential expression was called on offset fold change, offset = 20 (empirically determined) (18,25) calculated on the proximal ends of maximal confidence intervals built on the available replicates.…”
Section: Smallrnasmentioning
confidence: 99%
“…Among the many documented cases of loci contributing to natural variation (22), several examples of small regulatory RNAs have been described (23)(24)(25)(26). However, these examples involve changes in expression pattern of pre-existing micro-RNAs or creation of new target sites, rather than de novo generation of a small regulatory RNA, as observed with SULF.…”
mentioning
confidence: 99%